Silicone-containing hybrid polymer dispersions designed for coating applications - Kozakiewicz, J.; Zielecka, M.; Koncka-Foland, A.; Bujnowska, E.; Szulc, A. (Polimery, 2022)
The results of studies on novel aqueous silicone-containing hybrid polymer dispersions of specific architecture designed for coatings are presented. Dispersions were synthesized either via polymerization of acrylic and styrene monomers in aqueous poly(siloxaneurethaneurea) anionic dispersions prepared from the mixture of polysiloxanediol, saturated polyol and unsaturated polyol and cycloaliphatic diisocyanate or via polymerization of silicone monomers in commercially available acrylic copolymer dispersions. The effect of structural parameters of the hybrid polymers with constituted dispersion particles on the properties of dispersions, films and coatings was studied and it was found that they were significantly influenced by the share and kind of silicone component. More detailed studies of surface properties of the coatings using wettability determinations (DCA, SFE), ESCA, and AFM techniques revealed self-assembling of the surface layers depending on the chemical composition of the polymers constituting the hybrid system. The results show, that the macro-scale properties of hybrid materials (combination of organic polymers and silicones) can be tailored to the demands of particular application through designing of the specific micro- or even nano-scale architecture of the hybrid system.